(untitled) (Religious dialogue and cooperation, 2023)
The issue of violent manifestations in different social environments such as street, school or family constitutes a priority and a fundamental field, both for scientific research and for the intervention of competent institutions and personnel, in the context of contemporary societies, including the Romanian social space. Streets are a space for manifestations of violence that propagate in different registers. Deviant behaviour among students and, at the same time, among other categories of participants in educational and instructive activities significantly affects the school institution. In contrast to other social spaces, the school requires an immediate, appropriate, and particularly professional response.